Arsenic removal from acid extraction solutions of copper smelting flue dust. (10th February 2021) - Zheng, Guangya; Xia, Jupei; Liu, Hailang; Chen, Zhengjie
Abstract: Multi-metal extraction of flue dust from copper smelting is being pursued to meet the increasingly appealing environmental requirements of our modern life. In this paper, the thermodynamic analysis of acid leaching solution was carried out. Ferric arsenate deposits were found in the range of pH = 0–11.63, in the form of FeAsO4 and FeAsO4 ∙2H2 O. Cu2 AsO4 OH, CuHAsO4, and Cu5 H2 (AsO4 )4 forms of Cu2 AsO4 were produced in the range of pH = 0.98–2.33. Zn3 (AsO4 )2, Zn2 AsO4 OH, ZnHAsO4, and Zn5 H2 (AsO4 )4 forms of zinc arsenate were produced in the range of pH = 1.40–4.85. Theoretically, when pH = 0.98–2.33, copper arsenate salt was produced; however, when the actual experimental results were at pH ≥ 1.2, a small amount of copper co-settling occurred. Theoretical results were verified by single factor experiments. Strictly controlling the pH value of the reaction system can effectively separate arsenic (As) from copper (Cu) and zinc (Zn). Through single factor experimentation, optimal process parameters of iron salt and calcium salt combined with As removal were as follows: reaction time, 5 h; reaction temperature, 85 °C; pH value, 1.2; Fe–As molar ratio, 1.5; no H2 O2 added. Under these conditions, the precipitation rate of As was 89.12%, while Cu and Zn did not precipitate. Through XRD analysis, As element was removed from acid leaching solution in the form of scorodite (FeAsO4 ∙2H2 O). This has laid a theoretical foundation for the effective removal of As in acid leaching solution and the reduction of As content. Graphical abstract: Image 1 Highlights: The arsenic removal process of acid leaching solution was investigated. Arsenic can be removed in the form of scorodite (FeAsO4 ·2H2 O). The separation of As and Cu, Zn in acid solution was achieved. The mechanism for the arsenic removal in acid solution was proposed.